Assessing knowledge, attitudes, and practice of health providers towards the provision of postpartum intrauterine devices in Nepal: a two-year follow-up - Lucy Stone; Mahesh C. Puri; Muqi Guo; Iqbal H. Shah (BMC, 2021)
Abstract Background Health service providers play a key role in addressing women's need for postpartum pregnancy prevention. Yet, in Nepal, little is known about providers' knowledge, attitudes, and practice (KAP) on providing postpartum family planning (PPFP), particularly the immediate postpartum intrauterine device (PPIUD). This paper assesses providers KAP towards the provision of PPIUDs in Nepal prior to a PPIUD intervention to gain a baseline insight and analyzes whether their KAP changes both 6 and 24 months after the start of the intervention. Methods Data come from a randomized trial assessing the impact of a PPIUD intervention in Nepal between 2015 and 2017. We interviewed 96 providers working in six study hospitals who completed a baseline interview and follow-up interviews at 6 and 24 months. We used descriptive analysis, McNemar's test and the Wilcoxon signed-rank test to assess KAP of providers over 2 years. Results The PPIUD KAP scores improved significantly between the baseline and 6-month follow-up. Knowledge scores increased from 2.9 out of 4 to 3.5, attitude scores increased from 4 out of 7 to 5.3, and practice scores increased from 0.9 out of 3 to 2.8. There was a significant increase in positive attitude and practice between 6 and 24 months. Knowledge on a women's chance of getting pregnant while using an IUD was poor. Attitudes on recommending a PPIUD to different women significantly improved, however, attitudes towards recommending a PPIUD to unmarried women and women who have had an ectopic pregnancy improved the least. Practice of PPIUD counseling and insertion improved significantly from baseline to 24 months, from 10.4 and 9.4% to 99% respectively. Conclusions Although KAP improved significantly among providers during the PPIUD intervention, providers' knowledge on a women's chance of getting pregnant while using an IUD and attitudes towards recommending a PPIUD to unmarried women and women who have had an ectopic pregnancy improved the least. Provider KAP could be improved further through ongoing and more in-depth training to maintain providers' knowledge, reduce provider bias and misconceptions about PPIUD eligibility, and to ensure providers understand the importance of birth spacing.